EVALUASI KINERJA MODEL HUJAN ALIRAN LUMPED DALAM PENENTUAN ALIRAN DASAR DI DAERAH ALIRAN SUNGAI CITARUM - Brigita Diaz Primadita; M. Syahril Badri Kusuma; Waluyo Hatmoko (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2023)
ABSTRACT Studies related to baseflow modeling are still rarely carried out compared to flood modeling. The commonly used rainfall-runoff models oversimplify the baseflow process, which leads to poor low-flow simulations. Baseflow plays an important role in regulating the seasonal distribution of river flow, maintaining aquatic habitats, and transporting chemical nutrients in the river system. If the baseflow decreases in the Citarum Watershed, there will be consequential impacts on the Java-Bali electricity supply, rice field irrigation water, raw water, and industrial water in West Java and DKI Jakarta. This study evaluates six lumped-rainfall-runoff models that are popularly used in the Ministry of Public Works and Housing of Indonesia, namely Mock, NRECA, HBV96, NAM, Sacramento, and Empirical to simulate baseflow on the Nanjung Subwatershed and Cisokan Subwatershed. The baseflow simulations from each model are compared with the observational baseflow. The observational baseflow is obtained using the Recursive Digital Filter Lyne and Holick one filter methods. To quantify model comparison, a multi-criteria matrix is used consisting of the model convenience, baseflow parameters, and model performance. This study shows that the Mock Model gives the best results with a